HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI X IIS SMA KEMALA BHAYANGKARI - Rani, Shella Nurfiesta; Genjik, Bambang; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the relationship of learning motivation with student learning outcomes in economic subjects in class X IIS Kemala Bhayangkari 1 High School Kubu Raya. The research method used is descriptive method with the form of a study of relationship studies. The population in this study were 273 students and the sample was 38 students. Data collection used is indirect communication techniques (questionnaire sheets, questionnaire verification questions, as well as economic test questions) and documentary studies (student grade data). The results showed an average student learning motivation of 41.68 including the medium category, an average student learning outcome of 75.52, including the high category, and the relationship of learning motivation with student learning outcomes in economic subjects in class X IIS SMA Kemala Bhayangkari 1 Kubu Raya obtained a number of 0.003 which is smaller than the significance value of 0.05 and obtained an r count of 0.471989 which is greater than r table of 0.3120 so Ha is accepted and Ho is rejected. Correlation test results show the number 0.472. So the conclusion is learning motivation with student learning outcomes in economic subjects in class X Kemala Bhayangkari 1 Kubu Raya High School has a significant relationship with the level of category relations.Keywords: relationships, learning motivation, learning outcomes